2008
DOI: 10.1097/01.ta.0000240982.99842.b9
|View full text |Cite
|
Sign up to set email alerts
|

Can the Glenopolar Angle be Used to Predict Outcome and Treatment of the Floating Shoulder?

Abstract: The simple measurement of GPA may yield useful prognostic information and help in making decisions concerning the floating shoulder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 13 publications
1
29
0
Order By: Relevance
“…Pace et al [13] reported an average GPA value of 39°(range, 26-50°) measured in nine patients on AP radiographs of the non-affected shoulder as compared to our value of 36°(range, 28-46°). Kim et al [11] obtained an average GPA value of 38°(range, 35-42°) measured in 16 patients on AP chest radiographs of the non-affected side as compared to our measurement of 37°(range, 26-63°). We did not find any study dealing with normal GPA values based on Neer I views or on 3D CT reconstructions.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Pace et al [13] reported an average GPA value of 39°(range, 26-50°) measured in nine patients on AP radiographs of the non-affected shoulder as compared to our value of 36°(range, 28-46°). Kim et al [11] obtained an average GPA value of 38°(range, 35-42°) measured in 16 patients on AP chest radiographs of the non-affected side as compared to our measurement of 37°(range, 26-63°). We did not find any study dealing with normal GPA values based on Neer I views or on 3D CT reconstructions.…”
Section: Discussionmentioning
confidence: 95%
“…Subsequently, other authors measured the GPA in various radiological projections, i.e., on AP shoulder radiographs, Neer I scapular views and AP chest radiographs [2,4,8,[11][12][13]. None of the mentioned authors dealt with standardization of GPA measurements or the impact of projection on its values.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The glenopolar angle (GPA) is a well known standardized measurement which normal values oscillate between 30-45° [10,22]. When preserving a GPA above 30° is related with greater Constant Score (CST) [6,10,18,22]and Herscovici Score [10,20,22] demonstrated by some evidence III and IV studies.…”
Section: Glenoid Neck Fracturesmentioning
confidence: 99%
“…When preserving a GPA above 30° is related with greater Constant Score (CST) [6,10,18,22]and Herscovici Score [10,20,22] demonstrated by some evidence III and IV studies. Romero et al demonstrated that a GPA of less than 20° will produce persistent malrotation [4,6,23].…”
Section: Glenoid Neck Fracturesmentioning
confidence: 99%